2004
DOI: 10.1007/bf02708211
|View full text |Cite
|
Sign up to set email alerts
|

A study of partial molar volumes of citric acid and tartaric acid in water and binary aqueous mixtures of ethanol at various temperatures

Abstract: Partial molar volumes of citric acid and tartaric acid have been determined in water and binary aqueous mixtures of ethanol (5, 10, 15, 20 and 25% by weight of ethanol) at different temperatures and acid concentrations from the solution density measurements. The data have been evaluated by using Masson equation and the obtained parameters have been interpreted in terms of solute-solvent interactions. The partial molar volumes vary with temperature as a power series of temperature. Structure making/breaking cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 10 publications
(7 reference statements)
3
9
0
Order By: Relevance
“…Furthermore, it has also been observed that these values are independent of the nature of the drug. Similar observations have been reported by Parmar et al [14] for ammonium, sodium, and potassium phosphates in binary aqueous solutions of urea, and for citric acid and tartaric acid [15] in water and binary aqueous mixtures of EtOH at various temperatures in which S v values are reported to be negative. Also, for a number of hydrochloride-type drugs, either negative or very small values of S v have been reported in the literature [16], indicating weak ion-ion interactions.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, it has also been observed that these values are independent of the nature of the drug. Similar observations have been reported by Parmar et al [14] for ammonium, sodium, and potassium phosphates in binary aqueous solutions of urea, and for citric acid and tartaric acid [15] in water and binary aqueous mixtures of EtOH at various temperatures in which S v values are reported to be negative. Also, for a number of hydrochloride-type drugs, either negative or very small values of S v have been reported in the literature [16], indicating weak ion-ion interactions.…”
Section: Resultssupporting
confidence: 78%
“…Therefore, an appreciable inter-ionic penetration occurs and gives rise to negative slopes which leads to weak ion-ion interactions and strong ion-solvent interactions. These negative values of S v for different compositions also suggest the presence of cation-anion penetration [14,15], and this happens due to the competition between the drug ions to occupy the void space of the large solvent molecules. Also, it is seen (Tables 5-8) that there is no appreciable variation in S v with a change in composition of a particular aqueousalcoholic system, even when the alcohol component changes from MeOH to 1-PrOH.…”
Section: Resultsmentioning
confidence: 90%
“…Similar observations were reported by Parmar et al [28] of citric acid and tartaric acid in binary aqueous mixtures of ethanol at various temperatures using the negative S v values. However, at a particular temperature, with the increase of methanol content in aqueous methanol solution, V 0 / increases there by showing that solute-solvent interactions improve on the addition of more and more methanol in water [28]. From table 3, it is seen that the values of partial molar expansivity E 0 2 are positive indicating that the drug is a structure maker [29].…”
Section: Discussionsupporting
confidence: 87%
“…This is attributed to the fact that in a solvent of high dielectric constant like water, the solutes remain completely ionised even at fairly high concentration [27]. Similar observations were reported by Parmar et al [28] of citric acid and tartaric acid in binary aqueous mixtures of ethanol at various temperatures using the negative S v values. However, at a particular temperature, with the increase of methanol content in aqueous methanol solution, V 0 / increases there by showing that solute-solvent interactions improve on the addition of more and more methanol in water [28].…”
Section: Discussionsupporting
confidence: 79%
“…The concentration range used in the study was optimum for the validity of Staurdinger, Jone-Dole equation and Modified Jone-Dole equation in which it acts as structure maker. Further addition of solute can modify the structure of water by hydration as obtained volumetrically 10,11 from thermal expansion. The ratio of (B x /B) is 53.31, which is nearly equal to reported value for sugars 1 .…”
Section: Resultsmentioning
confidence: 99%